PERSON-JOB FIT AND EMPLOYEE ENGAGEMENT IN EDO STATE SECRETARIAT, BENIN CITY - OSAYANDE, Festus; OKOLIE, Ugo Chuks (Annals of Spiru Haret University. Economic Series, 2019)
Abstract In the last four decades, person-job fit, person-organization fit, job related attitudes and behaviours have remained topics of considerable interest in the fields of human resource management, organizational behaviour and industrial psychology. Person-job fit, which is the match between the individual’s knowledge, skills and abilities and the demands of the job positively, contributes to organizational attitudes and behaviour such as job satisfaction, job performance, employee’s commitment, display of organizational citizenship behaviour and employee’s engagement. This study therefore seeks to explore the nitty-gritty of person-job fit and its effect on employee engagement in Edo State Secretariat, Benin City using survey research method. Non-probabilistic sampling techniques comprising of purposeful and convenience techniques were used to elicit information via questionnaire from 250 respondents. Data collected were analyzed using descriptive statistics, correlation and linear regression analysis with the aid of Statistical Package for Social Science (SPSS) version 17. The results of the study showed that there is significant relationship between person-job fit and employee engagement. As predicted, the study also revealed that person-job fit exerts a positive and statistically significant effect on employee engagement. Thus, the study recommends among others that management should emphasize the suitability between job characteristics and employees ability to perform the job. This will go a long way to help employees recognize the similarity among them and thus exchange positive and supportive attitudes and behaviours.